A Fuzzy Logic-Based Tuning Model in an Indoor Lighting System for Energy and Visual Comfort Management - Wagiman, Khairul Rijal; Abdullah, Mohd Noor; Md Adnan, Mohd Faiz; Hussin, Imran; Aziz, Salmiah (International Journal of Integrated Engineering, 2023)
This paper proposes a fuzzy logic-based tuning model (FLTM) for daylight-linked control of the lighting system in an office room. The proposed FLTM considered a new method of dimming levels of light-emitting diode (LED) luminaires updating process to improve the performance of the developed fuzzy logic controller (FLC) in terms of energy consumption and visual comfort metric and, at the same time, fully complies with the European Standard EN 12464-1. The artificial lighting system and daylight simulation were carried out using DIALux to model artificial lighting and daylight illuminance levels matrices. The proposed FLTM was developed and simulated using MATLAB and validated and compared with other controllers, including developed FLC and artificial neural network (ANN) based control. The simulation results showed that the proposed FLTM successfully improved the performance of developed FLC in terms of a fully satisfied visual comfort set-point. It also attained higher energy savings of 2% than ANN and achieved the closest to preset visual comfort compared with other controllers. Moreover, the proposed method consumes less computational effort, and it is easy to integrate with developed FLC and daylight-linked control of the lighting system.